Efficacy of common salt application on the umbilical granuloma in infants - Faizan Sadiq; Ahmad, Khalil (Journal of the Pakistan Medical Association, 2023)
The objective of this study was to determine the efficacy of the application of common plain salt for the treatment of umbilical granuloma in infants. The study design was descriptive case series and was conducted over a period of 12 months at the paediatric unit, Mardan Medical Complex, Mardan, Pakistan. For this study a total of 50 infants with clinically evident umbilical granuloma were selected. Application of a pinch of common plain salt was advised on the granuloma twice a day for three consecutive days. Outcomes in the shape of complete resolution of the granuloma, adverse effects, and recurrence of granuloma were assessed. The number of patients responding well to the treatment was 45 (90%). The treatment showed good response and there was not any adverse effect or recurrence. ---Continue